Miniature Mobile Bristled In-Pipe Machine. (2nd December 2014) - Ostertag, Oskar; Ostertagová, Eva; Kelemen, Michal; Kelemenová, Tatiana; Buša, Ján; Virgala, Ivan
The in-pipe machine locomotes in the pipe on the principle of differential friction between the bristles and the pipe wall during the movement of the bristle forwards and backwards. These bristles are very important construction parts of the in-pipe machine. In order to define the locomotion of movement it is important to know the force situation on the bristles caused by its high deformation in the pipe. The determination of force situation brought us to a non-linear differential equation of the second order and determination of conditions for its solution. By this equation it is possible to describe the outline of large deformations of the construction part and to determine the forces affecting this part.